Acute hypoxia stress mediates HIF-1α-Yki-Cactus axis to facilitate the infection of Vibrio parahaemolyticus in Litopenaeus vannamei - He, Honghui; Huang, Shaoqing; Geng, Ningze; Weng, Shaoping; He, Jianguo; Li, Chaozheng (Frontiers in Immunology, 2024)
IntroductionHypoxia stress renders aquatic animals more susceptible to bacterial disease, yet the underlying mechanism remains elusive.MethodsWe conducted an acute hypoxia stress experiment to investigate the impact of stress on the immune response of Litopenaeus vannamei via transcriptome analysis, RT-qPCR and Western blot.ResultsOur results showed that acute hypoxia stress disrupted the tissue architecture, and significantly changed the gene expression profiles in the hepatopancreas of shrimp. More importantly, acute hypoxia stress significantly changed the expression levels of immune-related genes. Ladderlectin, GBP 1, Caspase-1, CLEC4F, MR1 and GBP 2 were significantly down-regulated, but HIF-1α, Cactus, TIPE, Akirin-2, Ivns1abp and TLR3 were significantly up-regulated. We further demonstrated that acute hypoxia activated Yki via HIF-1α to enhance expression level of Cactus, and then Cactus inhibited the phosphorylation of Dorsal and its nuclear translocation, thereby suppressing antibacterial immunity. Subsequently, the challenge experiment following stress revealed that exposure to acute hypoxia stress amplified the infectivity and lethality of Vibrio parahaemolyticus to shrimp. The mechanism of HIF-1α-Yki-Cautus axis provided an explanation for this phenomenon.DiscussionThis study offered new insights into interactions among environmental hypoxia stress, host immunity and pathogens, thereby providing practical guidelines for optimizing shrimp culture practices.